Determinant Factors of Company Value - Putri, Adetia; Muhammadinah, Muhammadinah; Shalihah, Bunga Mar’atush (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This study aims to analyze the effect of dividend policy and Corporate Social Responsibility on company value. The population of this study is food and beverage companies registered with ISSI for the 2019-2023 period totaling 30 companies. The sample was determined based on the criteria so that a sample of 9 food and beverage companies was obtained. The data was processed using multiple linear regression analysis using the Eviews application. The results of this study indicate that both partially and simultaneously the variables of dividend policy and Corporate Social Responsibility have a positive and significant effect on company value.